The effects of post-activation potentiation using resisted sled on sprint performance - Argeitaki, P.; Matiatos, G.; Paradisis, G.; Zacharogiannis, E.; Pilianidis, T.; Smirniotou, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction:The effects of resisting training program have been found to increase the rate of force development which is the main parameter that affects sprinting performance. Resisted sled is usually used in sprint training. The purpose of this study was to investigate the effects of post-activation potentiation (PAP) on sprinting using resisted sled (RS). Methods:Eleven sprint athletes, (mean ± SD: age 24,3 ± 3,1y, height 175,3 ± 6,6cm, body mass 71,2 ± 9,3kg and BMI 23,0 ± 1,5kg/m2) performed a 60m sprint from starting blocks before and after 40m run using a resisted sled. The intervention was consisted by a 40m run towing resisted sled (12% load of body mass) followed by a 5 min rest. The performance of 10m, 20m, 30m, 40m, 50m and 60m from the star line, was measured by 6 pairs of photocells (photocells, Microgate, It). A control group executed the same intervention without towing a resisted sled. A t-test for dependent samples was used (SPSS, Chicago, US). Results:The RS use improved significantly the performance in the 2nd 60m sprint compaired to the 1rst 60m sprint (p=0,000). The performance in the sections 0-30m, 0-40m, 0-50m were also improved significantly after towing RS (p=0,013, p=0,020, p=0,034 respectively). In contrast, there was not a significant improvement in sections 0-10m, 0-20m after towing the RS. The control group did not show any significant differences in all sections before and after the intervention condition without towing the resisted sled. Conclusion:The findings of this study indicate that the performance from 20 to 60m in a 60m sprint seems to be enhancing after a resisted training program using sled loaded with 12% of body mass. Thus, to obtain PAP a "resisted method" would be useful to be applied, in order to improve performance in sprinting although further research is required.